ONLINE GAMES AND COMMUNICATION BEHAVIOR OF MILLENNIAL MUSLIM TEENAGERS IN THE PERSPECTIVE OF COMMUNICATION PSYCHOLOGY - Fansauri, Hamzah; Faizah (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2023)
The majority of young people in Kekalek now find enjoyment and intriguing things to play in online games. It is unquestionably impossible to separate this action from the consequences, particularly the negative impacts of online gaming. The goal of this qualitative research method is to examine gamers' motivations for playing games and how they relate to their social behavior. The study's findings demonstrate that gamers play for enjoyment and entertainment, particularly when there is a competitive element. The implications also indicate a detrimental effect on gamers' communication behavior, including negative or sluggish reactions, disobeying parental commands, and using inappropriate language. As a result, gamers' primary objective is to enjoy themselves, which has an effect on the way they communicate, as they frequently use poisonous language and make fun of their parents and other members of the community.